Impacts of Digital Infrastructure and Renewable Energy on CO2 Emission Intensity: Evidence from 217 Countries - Nguyen, Nui Dang; Ngo, Phuong Kim; Pham, Quang Viet; Thai, Huyen Thu Thi; Doan, Anh Tuan Nguyen; Vu, Anh Linh; Tran, Tung Thanh (International Journal of Energy Economics and Policy, 2025)
This study investigates the effects of digital infrastructure and renewable energy consumption on CO₂ emission intensity across 217 countries from 1994 to 2023. Employing fixed effects and lagged panel regression models, the analysis reveals that broadband and internet usage are positively associated with CO₂ emission intensity, primarily due to the rising energy demands related to data infrastructure. In contrast, mobile subscriptions correlate with reduced emissions, suggesting gains in energy efficiency. Renewable energy consumption initially exhibits inefficiencies, contributing to higher emissions in the short term; however, it ultimately yields positive sustainability outcomes over time, particularly in high-income countries. The study also identifies significant heterogeneity across income groups, with low-income countries benefiting more environmentally from early-stage digital adoption. These findings underscore the need for differentiated digital and energy policy strategies tailored to a country's development level. The paper contributes to the literature by providing a comprehensive, data-driven analysis of the interplay between digitalization, renewable energy, and environmental efficiency. The insights support the formulation of targeted, evidence-based policies for advancing low-carbon, digitally inclusive development trajectories worldwide.